Exploring the Prevalence of Scabies Infestation among Madrasa Students in a Rural Area of Mymensingh District, Bangladesh - Begum, Maksuda; Hasan, AHM; Alam, Fakir Sameul; Dipu, Sultana Sobnam; Islam, Md Shahidul; Biswas, Binoy Krishna; Saha, Kamana Rani; Ali, Md Yunus (Community Based Medical Journal, 2025)
Scabies is a highly prevalent, neglected worldwide distributed disease of children as well as elderly population, attributed to overcrowding, low-socioeconomic status, close contact and lack of personal hygiene. A cross sectional, descriptive study was done among young madrasa students, in a rural area of Mymensingh district of Bangladesh, between July and October of 2022, to explore the prevalence of scabies. 178 students were enrolled in this study through purposive, random sampling method. Data were collected through direct interviewing of the respondents. Age of the participants ranged between 5 and 19 years with mean age 10.13±2.159 years; 10–14 years age group was predominate (52%). Female students (68%) were predominant over male students (32%). Male female ratio was 32:68. Primary level educated students were higher than the secondary level. 54% of the families of madrasa students were poor. A significant association (p<0.001) was revealed in between family status and scabies infestation. Literacy level of the father and the mother were found 55% and 57% respectively. Scabies cases were high among the students came from illiterate family. An association (p<0.001) revealed in between parents’ education and scabies. Scabies is a common health problem, high prevalent among the Madrasha students, attributed with personal hygiene, overcrowding, low socioeconomic status of family, illiteracy of parents and sharing of utensils among themselves. A large number of students knew the mode of transmission of scabies and importance of daily bathing; however, a significant number (65%) respondents did not know the value of not sharing the utensils among themselves. CBMJ 2025 July: vol. 14 no. 02 P:105-108